Analisis Teknik Camera Shot pada Film Surat Cinta untuk Starla Sutradara Rudi Aryanto - M Hendy Farrell M; Dani Manesah (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
The film Surat Cinta Untuk Starla, directed by Rudi Aryanto, employs a variety of camera shot techniques to explore the depth of its main characters and deliver powerful emotions to the audience. This study aims to analyze the use of camera shot techniques in the film, focusing on close-ups, medium shots, long shots, and tracking shots. These techniques are utilized to portray the characters' emotional expressions, interactions, and to enhance the theme of emotional journeys within the story. Through a qualitative approach with a literature review, the research highlights how camera shot techniques support the film's narrative and deepen the emotional connection between the audience and the characters. The analysis reveals that the appropriate choice of camera shot techniques can elevate the film's visual and emotional quality, creating a profound impact on the understanding of its story and characters.